Study on the Alleviation of Performance Degradation and Voltage Stability of PEMFC by Adding Silica Under Low-Temperature and Low-Humidity Conditions - Qiang Bai; Chuangyu Hsieh; Zhenghong Liu; Qipeng Chen; Fangbor Weng (Crystals)
This study enhances PEMFC performance at low temperature and low humidity by incorporating hydrophilic inorganic silica materials inside the PEMFC. Firstly, the polarization performance of the cell under varying humidity levels was investigated using a controlled variable method. Secondly, the power stability of the PEMFC was examined by observing voltage stability under constant current. Finally, the cell’s transient response at startup was studied. Experimental results indicate that the addition of silica partially mitigates the significant performance decline of the cell under a high humidity range (100% RH–50% RH). However, the effect is relatively average in a low humidity range (50% RH–20% RH).